Defining Long-Term Survivors Following Resection of Intrahepatic Cholangiocarcinoma - Bagante, F (2018)
BACKGROUND: Intrahepatic cholangiocarcinoma (ICC) is an aggressive primary tumor of the liver. While surgery remains the cornerstone of therapy, long-term survival following curative-intent resection is generally poor. The aim of the current study was to define the incidence of actual long-term survivors, as well as identify clinicopathological factors associated with long-term survival. METHODS: Patients who underwent a curative-intent liver resection for ICC between 1990 and 2015 were identified using a multi-institutional database. Overall, 679 patients were alive with ≥ 5 years of follow-up or had died during follow-up. Prognostic factors among patients who were long-term survivors (LT) (overall survival (OS) ≥ 5) were compared with patients who were not non-long-term survivors (non-LT) (OS < 5). RESULTS: Among the 1154 patients who underwent liver resection for ICC, 5- and 10-year OS were 39.6 and 20.3% while the actual LT survival rate was 13.3%. After excluding 475 patients who survived < 5 years, as well as patients were alive yet had < 5 years of follow-up, 153 patients (22.5%) who survived ≥ 5 years were included in the LT group, while 526 patients (77.5%) who died < 5 years from the date of surgery were included in the non-LT group. Factors associated with not surviving to 5 years included perineural invasion (OR 4.78, 95% CI, 1.92-11.8; p = 0.001), intrahepatic metastasis (OR 3.75, 95% CI, 0.85-16.6, p = 0.082), satellite lesions (OR 2.12, 95% CI, 1.15-3.90, p = 0.016), N1 status (OR 4.64, 95% CI, 1.77-12.2; p = 0.002), ICC > 5 cm (OR 2.40, 95% CI, 1.54-3.74, p < 0.001), and direct invasion of an adjacent organ (OR 3.98, 95% CI, 1.18-13.4, p = 0.026). However, a subset of patients (< 10%) who had these pathological characteristics were LT. CONCLUSION: While ICC is generally associated with a poor prognosis, some patients will be LT. In fact, even a subset of patients with traditional adverse prognostic factors survived long term.